PERAN PENDIDIKAN GIZI DALAM MENCEGAH STUNTING DI SEKOLAH DASAR - Anna Maria Oktaviani; Dhean Herdiansyah; Aini Anggraini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Nutritional problems that occur in Indonesia, including stunting or malnutrition, are a major challenge that can affect the quality of life, especially in elementary school children. Stunting is a health problem that often occurs in children, which is characterized by characteristics such as height below standard (shorter than their age), weight below standard, weak body immunity, slow bone growth reflecting chronic malnutrition that occurs which has an impact on physical and cognitive development in children. These symptoms occur due to a lack of balanced nutritional fulfillment during pregnancy and after childbirth so that the fulfillment of nutritional adequacy is not enough so that breast milk given to children under 2 years old is very vulnerable to stunting.